(untitled) - Kuper, Adam (Cambridge, Mass., 1994)
Is there a Darwinian explanation for the evolution of human nature? The great debates about human origins, cultural history, and human nature confront us with two opposing, often irreconcilable images of human beings: biology vs. culture. Now Kuper reframes these debates and reconsiders fundamental questions of anthropology. 21 halftones.
Keywords: Anthropology,Human beings,Culture